2014
DOI: 10.3389/fnhum.2013.00931
|View full text |Cite
|
Sign up to set email alerts
|

The medial habenula: still neglected

Abstract: The habenula is a small, bilateral brain structure located at the dorsal end of the diencephalon. This structure sends projections to the dopaminergic striatum and receives inputs from the limbic forebrain, making the habenula a unique modulator of cross-talk between these brain regions. Despite strong interest in the habenula during the seventies and eighties (Herkenham and Nauta, 1977; Beckstead, 1979; Beckstead et al., 1979; Herkenham and Nauta, 1979; Caldecott-Hazard et al., 1988), interest waned due to la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
125
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 88 publications
(115 reference statements)
0
125
0
5
Order By: Relevance
“…In contrast to the lateral habenula, the medial habenula is relatively understudied. It is a conserved region of the brain that has been considered as a part of the limbic circuits involved in the regulation of mood and stress (Morris et al, 1999;Hsu et al, 2014;Proulx et al, 2014;Viswanath et al, 2013).…”
Section: Gpr139 Is Activated By L-tryptophan and L-phenylalaninementioning
confidence: 99%
“…In contrast to the lateral habenula, the medial habenula is relatively understudied. It is a conserved region of the brain that has been considered as a part of the limbic circuits involved in the regulation of mood and stress (Morris et al, 1999;Hsu et al, 2014;Proulx et al, 2014;Viswanath et al, 2013).…”
Section: Gpr139 Is Activated By L-tryptophan and L-phenylalaninementioning
confidence: 99%
“…The LHb, which has pallidal and hypothalamic afferences and mainly projects to midbrain and hindbrain structures such as the raphe nuclei and VTA (Lecourtier and Kelly, 2007, Jhou et al, 2009, Kaufling et al, 2009, Kim, 2009), was shown involved in aversion and behavioral avoidance (Lammel et al, 2012, Stamatakis and Stuber, 2012, Ilango et al, 2013). The MHb receives septal inputs and projects primarily to the IPN, and has been less studied (Viswanath et al, 2013). This nucleus was proposed to regulate inhibitory controls, cognition-dependent executive functions, place aversion learning (Darcq et al, 2011, Kobayashi et al, 2013) and the nicotine withdrawal syndrome (Dani and De Biasi, 2013, Kobayashi et al, 2013, Dao et al, 2014).…”
mentioning
confidence: 99%
“…takođe, uočeno je povećanje metabolizma u MHb i interpedunkularnom jedru, kao njegovom glavnom ciljnom području, kao i smanjenje metaboličke aktivnosti u ventralnom tegmentalnom području, bazalnim ganglijama i amigdalama (49). Promene u MHb mogu biti posledica smanjene ekspresije interleukina-18, proinflamatornog citokina u gornjem subnukleusu ovog jedra (17,50). Pokazano je da su kod pacijenata obolelih od depresije u poređenju s kontrolnom grupom, zapremina i broj ćelija habenule smanjeni, kao i ćelijska površina medijalnog habenularnog jedra (51).…”
Section: Kontrola Sistema Zadovoljstva I Motornog Odgovoraunclassified
“…Poremećaj ovog balansa kod pušača vodi ka većoj konzumaciji nikotina, koja može da izazove selektivno oštećenje fasciculus retroflexusa, kao glavnog eferentnog puta habenule. Ovi rezultati ukazuju na to da su naChr receptori medijalnog habenularnog jedra uključeni u nastanak raznih oblika nikotinske zavisnosti (17) ekscesivni unos amfetamina i kokaina dovodi do poremećene dopaminske centralne regulacije i može dovesti do paranoje, deluzija, halucinacija i razvoja slike tzv. paranoidne shiofrenije.…”
Section: Uloga U Patogenezi Bolesti Zavisnostiunclassified
See 1 more Smart Citation